Reciprocal Regulation of KCC2 Trafficking and Synaptic Activity - Côme, Etienne; Heubl, Martin; Schwartz, Eric J.; Poncer, Jean Christophe; Lévi, Sabine (Frontiers in Cellular Neuroscience, 2019)
The main inhibitory neurotransmitter receptors in the adult central nervous system are type A γ-aminobutyric acid receptors (GABAAR) and glycine receptors (GlyR). Synaptic responses mediated by GlyR and GABAAR display a hyperpolarizing shift during development. This hyperpolarization relies mainly on the developmental up-regulation of the K+-Cl- co-transporter KCC2 responsible for the extrusion of Cl-. In mature neurons, altered KCC2 function - mainly through increased endocytosis - leads to the re-emergence of depolarizing GABAergic and glycinergic signaling, which promotes hyperexcitability and pathological activities. Identifying signaling pathways and molecular partners that control KCC2 surface stability thus represents a key step in the development of novel therapeutic strategies. Here, we present our current knowledge on the cellular and molecular mechanisms governing the plasma membrane turnover rate of the transporter under resting conditions and in response to synaptic activity. We also discuss the notion that KCC2 lateral diffusion is one of the first parameters modulating the transporter membrane stability, allowing for rapid adaptation of Cl- transport to changes in neuronal activity.